2017
DOI: 10.1371/journal.pone.0186258
|View full text |Cite
|
Sign up to set email alerts
|

Serial-omics characterization of equine urine

Abstract: Horse urine is easily collected and contains molecules readily measurable using mass spectrometry that can be used as biomarkers representative of health, disease or drug tampering. This study aimed at analyzing microliter levels of horse urine to purify, identify and quantify proteins, polar metabolites and non-polar lipids. Urine from a healthy 12 year old quarter horse mare on a diet of grass hay and vitamin/mineral supplements with limited pasture access was collected for serial-omics characterization. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…Yuan et al used an orthogonal ionisation approach to investigate the health status of the equine athlete when targeting compounds such as proteins, lipids and small polar metabolites. 134 The one-horse urine study revealed 46 proteins, 10 lipids and 474 small polar metabolites, which are indicative of a healthy mare. These findings can be used to track the health status of horses, specifically mares, and for future reference to other administration or health studies as a comparative measure.…”
Section: Equine Anti-dopingmentioning
confidence: 98%
See 3 more Smart Citations
“…Yuan et al used an orthogonal ionisation approach to investigate the health status of the equine athlete when targeting compounds such as proteins, lipids and small polar metabolites. 134 The one-horse urine study revealed 46 proteins, 10 lipids and 474 small polar metabolites, which are indicative of a healthy mare. These findings can be used to track the health status of horses, specifically mares, and for future reference to other administration or health studies as a comparative measure.…”
Section: Equine Anti-dopingmentioning
confidence: 98%
“…12 Common metabolomics studies of the equine athlete look at its exercise physiology, and therefore, metabolites are measured for energy production and utilisation. 12,134 Investigations into the health status of an equine athlete will provide information on biomarkers of disease and healthy athletes. Yuan et al used an orthogonal ionisation approach to investigate the health status of the equine athlete when targeting compounds such as proteins, lipids and small polar metabolites.…”
Section: Equine Anti-dopingmentioning
confidence: 99%
See 2 more Smart Citations
“…The establishment of normal urinary protein profiles is critical for further investigation of diagnosing and monitoring the progression of diseases 4 . There has been normal urinary proteomics investigated in many species including human 3 , cattle 5 and horses 6 . In healthy cows, 1564 urinary proteins in total are identified and the majority proteins are categorized into cytoplastic, catalytic activity and metabolism 5 .…”
Section: Introductionmentioning
confidence: 99%